MANAJEMEN KURIKULUM PROGRAM TAHFIDZ DI PONDOK PESANTREN AL WAFA PUTRI PALANGKA RAYA - Yuliana Agustin; Sapuadi Sapuadi; Nurul Hikmah (STKIP Pesisir Selatan, 2025)
Curriculum management plays a crucial role in supporting the success of the tahfidz program in Islamic educational institutions. This article aims to describe the curriculum management of the tahfidz program at the Al Wafa Putri Islamic Boarding School in Palangka Raya, focusing on three main aspects: planning, organization, and implementation. This research employs a qualitative approach with a case study, while data collection was conducted through interviews, observation, and documentation. Data validation was ensured by source and technique triangulation. The research results show that curriculum planning is carried out through deliberation between the Islamic boarding school leadership and the tahfidz teachers, encompassing goal setting, content determination, learning methods, learning resources, and evaluation. Organization begins with a Qur'an reading ability test, followed by the formation of halaqah (teaching circles) and the placement of teachers according to their expertise. Program implementation is carried out in a scheduled and intensive manner using the sabaq, talaqqi, sabqi, and muraja'ah methods. These findings indicate that the success of the Al Wafa Putri tahfidz program is largely determined by the accuracy of curriculum management, from adaptive planning and effective organization to consistent implementation. The success of the tahfidz program is measured not only by the quantity of memorization, but also by the accuracy of recitation, mastery of tajwid, and the strength of memorization (mutqin).